Combining ability and heterosis for grain yield and yield component traits in maize (Zea mays L.) - V. Shasi Kiran Reddy, Digbijaya Swain*, Saswaty Priyadarshini Sahoo, Arjun Kumar Agarwal, Devraj Lenka, Mihir Ranjan Mohanty and Mandakini Kabi (Electronic Journal of Plant Breeding)
The present investigation was conducted on maize hybrids to determine the extent of heterosis and combining ability for 12 quantitative traits including yield and its contributing traits during Kharif, 2021. A set of 28 F1s developed by 8 x 8 half diallel mating design and the resultant hybrids along with parents and standard checks were evaluated in Randomised Block Design (RBD) with three replications. For standard heterosis over hybrid Bio 9544 ranged from 11.10 to 44.86 % and four F1 cross combinations (SNL 142828-4 x CML 451, CAL 1473-4 x CML 451, CAL 1424-1 x CML 470-1 and SNL 142828-4 x CML 470-1) exhibited standard heterosis of 10 % or more for grain yield/ ha. On the basis of general combining ability (gca) estimates, V351 was the best general combiner followed by CML 451 for grain yield/ ha. Considering the per se performance, standard heterosis and specific combining ability (sca) effects, the four hybrids i.e., SNL 142828-4 x CML 451, CAL 1473-4 x CML 451, CAL 1424-1 x CML 470-1 and SNL 142828-1 x CML 470 1 were identified as promising for exploiting heterosis for grain yield.